1992
DOI: 10.1901/jaba.1992.25-385
|View full text |Cite
|
Sign up to set email alerts
|

Training Supervisors in a Collaborative Team Approach to Promote Peer Interaction of Children With Disabilities in Integrated Preschools

Abstract: Three supervisors of integrated preschools were trained in a collaborative team approach to encourage resource and classroom teachers to develop strategies that promote peer interaction of all children, including children with disabilities. The focus of classroom teachers' behaviors and the interactive play of children with disabilities were measured daily in both a training (indoor play period) and a generalization (outdoor play period) setting. In a multiple baseline design, supervisors were individually tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…This process located 383 potential supervision reports for inclusion, of which N ¼ 24 satisfied the nine inclusion criteria. These studies were: Demchak and Browder (1990), Ducharme, Williams, Cummings, Murray, and Spencer (2001), Fleming, Oliver, and Bolton (1996), Gillam et al (1990), Hansebo and Kihlgren (2004), Harchik, Sherman, Sheldon, and Strouse (1992), Harkness (1995Harkness ( , 1997, Harkness and Hensley (1991), Hundert and Hopkins (1992), Jenson, Parsons, and Reid (1998), Methot, Williams, Cummings, and Bradshaw (1996) Schepis and Reid (1994), Shlomskas et al (2005) and Shore, Iwata, Vollmer, Lerman, and Zarcone (1995). These studies included 13 consultants, 72 supervisors, 499 supervisees and 711 patients.…”
Section: Procedures and Reliabilitymentioning
confidence: 99%
“…This process located 383 potential supervision reports for inclusion, of which N ¼ 24 satisfied the nine inclusion criteria. These studies were: Demchak and Browder (1990), Ducharme, Williams, Cummings, Murray, and Spencer (2001), Fleming, Oliver, and Bolton (1996), Gillam et al (1990), Hansebo and Kihlgren (2004), Harchik, Sherman, Sheldon, and Strouse (1992), Harkness (1995Harkness ( , 1997, Harkness and Hensley (1991), Hundert and Hopkins (1992), Jenson, Parsons, and Reid (1998), Methot, Williams, Cummings, and Bradshaw (1996) Schepis and Reid (1994), Shlomskas et al (2005) and Shore, Iwata, Vollmer, Lerman, and Zarcone (1995). These studies included 13 consultants, 72 supervisors, 499 supervisees and 711 patients.…”
Section: Procedures and Reliabilitymentioning
confidence: 99%
“…It can be seen that data on the level of competence of the supervisors are lacking, even when the studies analysed experienced professional supervisors (e.g. Alpher, 1991 ;Friedlander, Siegel, & Brenock, 1989 ;Hundert & Hopkins, 1992). Instead, studies at best reported that the supervisors were`experienced ' or provided data on the supervisors' time in post (Parsons, Reid, & Green (1993, p. 173) stated that ¼ supervisors¼ had an average of 15 months experience ', for example).…”
Section: Prediction 1 : Information On the Participants Will Be Sketcmentioning
confidence: 99%
“…Data for the Activities condition showcd a de- the use o f a lead teacher to maintain the more effcctive condition may be an important strategy for use in the organization o f center-based programs. Supervisor training and its effects on teachers and preschool children was reported by Hundert and Hopkins (1992). They used role playing, coaching, and feedback to prepare supervisors who subsequently worked with classroom and consultant teachers to alter child-centered interventions.…”
Section: Journal Of Applied Behavior Arialysis and Journal Of Organizmentioning
confidence: 99%